Develop a robust nonlinear controller for large aircraft by applying NDI, SMC and adaptive control - Zeng, Chao (Cranfield University, 2012)
A nonlinear dynamic inversion (NDI) controller and a sliding mode controller are developed for large civil transport Boeing 747 in this thesis. Furthermore adaptive control theory is applied on both NDI controller and SMC controller to improve the performance. Nonlinear dynamic inversion is an advanced control method which is able to directly handle nonlinear system with less gain schedule and provides inherent decoupled property. The system is linearized as a pure integrator by inner loop feedback, whilst the desired control law is fulfilled by the outer loop linear controller. However, the NDI controller is considerably sensitive to uncertainty due to the incomplete cancellation. SMC, a well known nonlinear robust control method, is utilized to endow the controller with more robustness. The results show that SMC controllers perform better than NDI controllers, but are still not perfect. Finally, a parameter on-line estimation adaptive scheme is applied to improve NDI controller meanwhile a disturbance observer is designed in addition to SMC controller. It is drawn from assessments that the disturbance observer based SMC controller achieves the best performance for all flight points: fast rising-up speed, little overshoot, short settle time and very small steady state error. In addition, the classical and modern linear control theories as well as nonlinear control methods are reviewed. Moreover, some flying and handling quality criteria are also given as literature review.